2011
DOI: 10.1021/jo200482d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Conformationally Preorganized, (R)-Diethylene Glycol-Containing γ-Peptide Nucleic Acids with Superior Hybridization Properties and Water Solubility

Abstract: Developed in the early 1990's, PNA has emerged as a promising class of nucleic acid mimic because of its strong binding affinity and sequence selectivity towards DNA and RNA, and resistance to enzymatic degradation by proteases and nucleases; however, the main drawbacks, as compared to other classes of oligonucleotides, are water solubility and biocompatibility. Herein we show that installation of a relatively small, hydrophilic (R)-diethylene glycol (`miniPEG') unit at the γ-backbone transforms a randomly-fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
263
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(281 citation statements)
references
References 99 publications
(183 reference statements)
14
263
1
3
Order By: Relevance
“…This is similar to the 2x excess of PNApeptide required for quantitative binding to the same DNA nanocage. 22 Some PNA sequences show mild aggregation at concentrations as low as 1 mM, 24 which could prevent binding of some PNA to the DNA nanocage. The larger excess required for g-PNA1 may be due to its reduced solubility compared to g-PNA3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is similar to the 2x excess of PNApeptide required for quantitative binding to the same DNA nanocage. 22 Some PNA sequences show mild aggregation at concentrations as low as 1 mM, 24 which could prevent binding of some PNA to the DNA nanocage. The larger excess required for g-PNA1 may be due to its reduced solubility compared to g-PNA3.…”
Section: Resultsmentioning
confidence: 99%
“…The assembly process was rapid and could be performed at or below room temperature, providing mild conditions that preserved the function of the attached polypeptides. Substitutions to the gamma position on the PNA backbone (see Figure S2) have been shown to increase the solubility and thermal stability of the PNA strand, 24 as well as provide a handle to introduce functional groups without affecting its binding to a complementary strand. 25 Functionalizing PNA at the gamma position would also allow a peptide to be connected anywhere along the backbone or even at multiple locations to form stable cyclic PNA-peptides.…”
Section: Introductionmentioning
confidence: 99%
“…16 Also, preorganization resulting from a simple substitution at the γ-position in aegPNA significantly improves its binding properties. 17 Various substituents can be placed at this position to improve water solubility 18 or cell penetration 19,20 or to incorporate other functions. 21,22 Because of its straightforward access via proline derivatives having well-defined stereochemistries, the pyrrolidine ring has been extensively used as a constraint element in the design of new PNA structures ( Figure 3).…”
Section: Conformationally Constrained Pnamentioning
confidence: 99%
“…In essence, this PNA structure, termed gPNA, is the first PNA oligomer to have sequenceunrestricted invasion capabilities while maintaining single base-pair specificity (Chenna et al, 2008;He, Rapireddy, Bahal, Sahu, & Ly, 2009). In addition, in order to address the issue of solubility using gPNAs, Sahu et al demonstrated that by incorporating, at the g-position of the backbone a diethylene glycol moiety, this results in a significant increase in solubility while not adversely affecting affinity or sequence specificity (Bahal, Sahu, Rapireddy, Lee, & Ly, 2012;Sahu et al, 2011).…”
Section: The Many Flavours Of Artificial Nucleic Acids; Different Strmentioning
confidence: 99%